Structure of nonintegrated, circular Herpesvirus saimiri and Herpesvirus ateles genomes in tumor cell lines and in vitro-transformed cells. - Kaschka-Dierich, C (1982)
Nonintegrated, circular DNA molecules of Herpesvirus saimiri and Herpesvirus ateles were found in five lymphoid cell lines originating from tumor tissues or established by in vitro immortalization of T lymphocytes. The arrangement of unique (L) and repetitive (H) DNA sequences in circular viral genomes was analyzed by partial denaturation mapping followed by visualization with an electron microscope. Three types of circular viral DNA structures were found. (i) The virus-producing cell line RLC, which is derived from an H. ateles-induced rabbit lymphoma, contains circular viral genomes which consist of a single L-DNA and a single H-DNA region, both the same length as in virion DNA. (ii) The circular viral genomes of the nonproducer cell lines H1591 and A1601, in vitro transformed by H. saimiri and H. ateles, respectively, have deletions in the unique L-DNA region and larger H-DNA regions. Cell line A1601 lacks about 8% of virion L-DNA, and H1591 cells lack about 40% of viral L-DNA information. (iii) The nonproducing H. saimiri tumor cell lines 1670 and 70N2 harbor viral genomes with two L-DNA and two H-DNA regions, respectively. Both types of circular molecules have a long and a short L-segment. The sequence arrangements of circular DNA molecules from H. saimiri-transformed cell lines were compared with those of linear virion DNA by computer alignment of partial denaturation histograms. The L-DNA deletion in cell line H1591 was found to map in the right half of the virion DNA. Comparison of the denaturation patterns of both L regions of cell lines 1670 and 70N2 identified the short L regions as subsets of the long L regions. Thus, circular viral DNA molecules of all four nonproducer cell lines represent defective genomes.